The Importance of Women’s Education. Why Should We Educate Women? - Maftuna Makhkamova Shavkat qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Over the past decades, significant strides have been made in the field of education. Countries worldwide, whether developed or developing, are attempting to provide opportunities for individuals to access quality education, irrespective of social, economic, or religious backgrounds. However, gender inequality persists. According to UNICEF, around the world, 119 million girls are out of school, including 34 million of primary school age and 87 million of secondary school age (UNICEF, 2024) [1]. This article discusses the challenges and benefits of educating women. "Give me an educated mother, I shall promise you the birth of a civilized, educated nation." – Napoleon Bonaparte.